2017
DOI: 10.1515/biolog-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Citrus flavonoids collectively dominate the α-amylase and α-glucosidase inhibitions

Abstract: A series of citrus flavonoids were evaluated for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Naringin, as reported by Sahnoun et al (2017), showed an excellent inhibition for α-amylase and α-glucosidase enzyme, with IC 50 values of 8.0 μM and 0.55 μM, respectively. Lim et al (2018) studied the protective effects and molecular mechanisms of naringin in diabetic mice.…”
Section: Naringeninmentioning
confidence: 55%
See 1 more Smart Citation
“…Naringin, as reported by Sahnoun et al (2017), showed an excellent inhibition for α-amylase and α-glucosidase enzyme, with IC 50 values of 8.0 μM and 0.55 μM, respectively. Lim et al (2018) studied the protective effects and molecular mechanisms of naringin in diabetic mice.…”
Section: Naringeninmentioning
confidence: 55%
“…The metabolic effects of hesperidin were also demonstrated by Sahnoun et al (2017) and Zeng et al (2018), who reported its ability to inhibit α-amylase, α-glucosidase, and lipase enzyme with the IC 50 values of 111 and 1 μM, and 688.25 μg/mL, respectively. In a randomized double-blind controlled clinical trial design, 23 subjects with T2DM consumed 500 mg/day hesperidin supplement for 8 weeks.…”
Section: Hesperidinmentioning
confidence: 75%
“…Apigenin and phloretin were reported to reversibly inhibit α-glucosidase activity [31,32] . Tangeretin and rhoifolin were found to inhibit α-glucosidase and α-amylase activity [33] . The OGTT test was conducted to evaluate the hypoglycemic potential of these extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present work are in agreement with previous reports on raw citrus samples. Citrus flavonoids have shown carbohydrase inhibition capacity [31]. Citrus × clementina Hort.…”
Section: Bioaccessibility Of Inhibitors Of the Enzymes α-Glucosidase And α-Amylase Composing Citrus Pomacesmentioning
confidence: 99%